2015
DOI: 10.18632/oncotarget.5569
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis reveals bilateral breast cancers are genetically independent

Abstract: Bilateral breast cancer (BBC) poses a major challenge for oncologists because of the cryptic relationship between the two lesions. The purpose of this study was to determine the origin of the contralateral breast cancer (either dependent or independent of the index tumor). Here, we used ultra-deep whole-exome sequencing and array comparative genomic hybridization (aCGH) to study four paired samples of BBCs with different tumor subtypes and time intervals between the developments of each tumor. We used two pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…[10][11][12] Some recent studies addressed the idea of a possible clonal origin of some subsets of tumors such as bilateral breast cancer or SCRC using mutational concordance or clonality analysis by means of copy number profiles and concluded that paired tumors were different in origin. [13][14][15] However, this conclusion should be considered cautiously given the limited sample size of these studies. Nevertheless, if a subset of SCRC fulfill clonality features, this should have not only therapeutic implications (treating different or similar paired tumors in the same patient), but it could also imply changes in the intrinsic definition of SCRC.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[10][11][12] Some recent studies addressed the idea of a possible clonal origin of some subsets of tumors such as bilateral breast cancer or SCRC using mutational concordance or clonality analysis by means of copy number profiles and concluded that paired tumors were different in origin. [13][14][15] However, this conclusion should be considered cautiously given the limited sample size of these studies. Nevertheless, if a subset of SCRC fulfill clonality features, this should have not only therapeutic implications (treating different or similar paired tumors in the same patient), but it could also imply changes in the intrinsic definition of SCRC.…”
Section: Introductionmentioning
confidence: 97%
“…Comparative analyses of SCRCs have been carried out frequently, especially focused on MSI or CIMP, or somatic mutations, with conflicting results . Some recent studies addressed the idea of a possible clonal origin of some subsets of tumors such as bilateral breast cancer or SCRC using mutational concordance or clonality analysis by means of copy number profiles and concluded that paired tumors were different in origin . However, this conclusion should be considered cautiously given the limited sample size of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies employed genome-wide copy number arrays permitting, in principle, greater resolution and a more definitive test for clonal relatedness, but were often hampered by the use of deoxyribonucleic acid (DNA) obtained from paraffin-embedded tissues. 21,22 Three recent studies used mutational data derived from whole-exome sequencing for clonality analyses, [23][24][25] and an additional study examined chromosomal rearrangements in 10 cases using low coverage whole genome sequencing. 26 In the largest of these studies, Klevebring et al examined 25 metachronous breast cancers and concluded that 3 (12%) were clonally related.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with microarrays, NGS is able to detect RNAs with very low expressions and identify unrecognized novel targets [7], as well as providing more detailed information [8]. Several previous studies [9][10][11][12][13][14][15][16] used NGS to seek mutations and differentially expressed genes (DEGs) that could play pivotal roles in the colorectal carcinogenesis and metastases, which reveals the significance of NGS.…”
Section: Introductionmentioning
confidence: 99%